ISLAMIC SOCIAL FINANCE AND THE SUSTAINABLE DEVELOPMENT GOALS (SDGs): A STRATEGIC FRAMEWORK FOR INCLUSIVE DEVELOPMENT - Fadil, Cholid; Harya, Gyska Indah (Penelitian dan Pengembangan Ilmu, 2026)
The achievement of the Sustainable Development Goals (SDGs) faces significant challenges due to a global financing gap estimated at USD 4.2 trillion annually. This study aims to formulate a strategic framework for Islamic Social Finance (ISF), which includes zakat, infaq, sadaqah, and waqf (ZISWAF), as an instrument for financial inclusion and sustainable development. This study employs a narrative review method with a comprehensive approach by synthesizing literature published over the last ten years from the Scopus, Web of Science (WoS), and Google Scholar databases, with a comparative focus on the ISF ecosystem in Indonesia, Malaysia, and the Gulf Cooperation Council (GCC) countries. The findings indicate that the effectiveness of ISF in supporting the achievement of the SDGs, particularly poverty alleviation (SDG 1) and inequality reduction (SDG 10), is highly dependent on governance reforms. Digital transformation through fintech and blockchain is identified as a key catalyst in strengthening transparency (shafafiyah) and accountability (mas’uliyah). In addition, the shift from consumptive assistance models toward productive economic empowerment and waqf-based investment has been shown to generate more measurable long-term social impacts. This study concludes that the integration of maqasid al-shariah principles with modern governance constitutes a fundamental prerequisite for ISF institutions to create inclusive, equitable, and sustainable welfare distribution.